Commodification of Padel Sports as A Culture of Capitalism and Personal Branding on Instagram - Rahmadiana Rahmadiana; Dani Siswardhani Wahjono (PT Agung Media Publisher, 2025)
The rapid expansion of digital platforms has transformed sport from a physical and recreational practice into a symbolic and economic resource within digital capitalism. In Indonesia, padel has emerged as a lifestyle sport closely associated with urban elites and Instagram-based self-presentation. This study examines how padel is commodified as a cultural practice and mobilized as a personal branding strategy through visual representations on Instagram. This research adopts a qualitative approach using digital visual content analysis. Data consist of Instagram posts related to padel activities uploaded by Indonesian influencers and public figures between April and July 2025. The analysis integrates Roland Barthes’ semiotic framework to examine denotative, connotative, and mythic meanings, alongside Mosco’s political economy of communication to contextualize these representations within the structural logic of digital capitalism. The findings reveal that padel is represented less as a competitive sport and more as a cultural commodity embedded in luxury consumption, aesthetic coherence, and emotional display. Visual elements such as premium venues, branded equipment, fashionable attire, and expressions of joy and confidence construct padel as a marker of prestige, modernity, and social distinction. Influencers strategically integrate padel into lifestyle narratives, transforming leisure activities into symbolic and economic capital within Instagram’s attention economy. These findings indicate that padel functions as a performative space where identity, emotion, and consumption intersect under platform capitalism. The commodification of padel reflects broader dynamics of cultural and emotional capitalism, in which emotions and authenticity are instrumentalized for visibility and engagement.